The effect of financial knowledge, financial planning, internal locus of control, and financial self-efficacy on financial management behaviour: A case study of SMEs Grocery Stores - Dias Setianingsih; Meutia Dewi; Ayu Chanda (Fakultas Ekonomi Universitas Samudra, 2022)
This study examines the effect of financial knowledge, financial planning, internal locus of control and financial self-efficacy on financial management behaviour in SMEs Grocery Stores in Langsa City. The population in this study amounted to 159 SMEs grocery stores and the sample amounted to 114 SMEs grocery stores. The sampling technique was carried out by purposive sampling technique. The data analysis method used is the multiple linear regression method. The hypothesis testing variables X1 and X3 have a significant effect on variable Y. In contrast, variables X2 and X4 have no significant effect on variable Y. Variable X3 has a value of 0.001 < 0.05, which means that variable X3 has a significant effect on variable Y. The coefficient of determination test results shows that the value is 24.9 %, and the remaining 75.1% is influenced by other factors not examined in this study.